Quality Schools From an Educational Policy Point of View Independent Learning in Indonesia - Roce Marsaulina; Dan Kia; Sri Rezeki (JURNAL KADESI, 2023)
The current independent curriculum hopes to present a form of education that can compete globally. The curriculum framework is flexible and prioritizes character development as the main subject. The problem is how to form the behavior habits of each student so that they have a moral character and are not easily swayed by the challenges of the times. The author uses a qualitative descriptive method. Procedurally, the adaptation of the independent curriculum begins with a study of the concept of independent learning activities on independent campuses that involve planning, learning processes, assessments, and learning evaluations. Then look at the suitability of the existing study program curriculum based on KKN. In implementing an independent curriculum, each campus must be able to facilitate student rights. This is the vision of the Ministry of Education and Culture to realize an advanced Indonesia that is sovereign, independent, and has personality through the creation of Pancasila Students who think critically, creatively, independently, and have faith in God Almighty, with noble character, cooperation, and global diversity, can be achieved through Freedom of Learning policy. The integrity of students is also formed to be responsible for their academic status so that they can innovate and compete globally and benefit the social environment.